2011
DOI: 10.3855/jidc.1667
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of severe acute rotavirus gastroenteritis and intussusceptions in Ghanaian children under 5 years of age

Abstract: Introduction: Vaccination is the most effective preventive strategy against rotavirus disease. Regional differences in prevalent rotavirus genotypes may affect vaccine efficacy. Pre-vaccine surveillance for burden of rotavirus disease, prevalent rotavirus genotypes, and association between rotavirus disease and intussusceptions helps in monitoring the impact of vaccination. Methodology: A prospective study was conducted from January 2008 to December 2009 in children younger than five years hospitalized for lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 31 publications
5
16
0
1
Order By: Relevance
“…However, Ho et al reported 952 intussusception cases in Taiwan from 1999 to 2001, and they concluded that there was no seasonal trend [12]. Enweronu-Laryea et al reported no intussusception seasonality in a 5-year study of Ghanaian children [13]. Khumju et al reported 72 intussusception cases over 3 years in Thailand finding that the peak of intussusception incidence for this sample was in the winter [14].…”
Section: Discussionmentioning
confidence: 83%
“…However, Ho et al reported 952 intussusception cases in Taiwan from 1999 to 2001, and they concluded that there was no seasonal trend [12]. Enweronu-Laryea et al reported no intussusception seasonality in a 5-year study of Ghanaian children [13]. Khumju et al reported 72 intussusception cases over 3 years in Thailand finding that the peak of intussusception incidence for this sample was in the winter [14].…”
Section: Discussionmentioning
confidence: 83%
“…9,16,[19][20][21][22][23][24][25] In developed countries, in europe particularly, studies have shown that the prevalence varied between 41% and 46%. 2,6,7,10,26,27 the high prevalence of rotavirus gastroenteritis globally suggests that, unlike for other causes of gastroenteritis, improved sanitary conditions will probably not be enough to fight against rotavirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…13,16,19,20,23,24 Current rotavirus vaccines were shown to provide broad heterotypic protection against a wide variety of circulating strains in clinical trials. 4,18,[36][37][38] Given the yearly changes in circulating genotypes and the enormous diversity observed, evaluating the performance and impact of rotavirus vaccines and monitoring circulating strains pre-and postrotavirus vaccine introduction would be important in countries like togo with great strain diversity.…”
Section: Number Of Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization (WHO) has encouraged the introduction of a rotavirus vaccine into national immunisation programs, particularly in poorer countries [6]. Pre-vaccine surveillance to estimate the burden of rotavirus disease, prevalent rotavirus genotypes and the association between rotavirus disease and intussusceptions helps in monitoring the impact of vaccination [7].…”
Section: Introductionmentioning
confidence: 99%